Analyzing the multilevel interventions for effective implementation of social and emotional learning in the Jordanian school curriculum - Hena Ahmed Iraqui; Muraina Kamilu Olanrewaju (International Journal on Education Insight, 2026)
Social and emotional learning (SEL) programs are increasingly recognized for their critical role in fostering the holistic development of students. This paper evaluates the benefits of SEL and explores its integration into the Jordanian school curriculum, emphasizing the need for culturally responsive and context-specific approaches. Through a comparative analysis of leading SEL frameworks, such as the Collaborative for Academic, Social, and Emotional Learning (CASEL) and the Strong Start in the US, the Promoting Alternative Thinking Strategies (PATHS) in the UK, the Strong Kids in Hong Kong, and the OECD’s Social and Emotional Skills framework, this study identifies key components and implementation strategies that have shown effectiveness in various educational contexts. Each of these programs offers unique insights into age-appropriate design, instructional delivery, and outcome measurement. This cross-contextual analysis reveals that successful SEL implementation in Jordan requires a multi-level approach involving curriculum integration, teacher training, community and parental engagement, and supportive policy frameworks. The paper argues that while international models provide evidence-based guidance, a localized adaptation is essential for relevance and sustainability. Ultimately, the study concludes that embedding SEL into Jordan’s education system will not only enhance academic outcomes and emotional resilience but also contribute to the broader goals of student well-being, social cohesion, and future readiness. The paper suggested the need to invest in pre-service and in-service training for educators on SEL competencies and delivery methods.